Pemaknaan Nasionalisme Budaya dalam Iklan (Studi Resepsi pada iklan Grab versi #ModalPercaya dan Shopee Versi #ArtiNasionalisme) - Jatisidi, Artyasto (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2023)
Globalization has influenced the current nationalism of Indonesia, where the nation's nationalism is far removed from its original meaning. Symbols of global cultural products seem to overshadow the sense of identity of the entire young generation of Indonesia. On the other hand, mass media also plays a role in this by creating false and misleading awareness about the values of nationalism, one of which is through television advertisements. The aim of this research is to understand how contemporary nationalism, as perceived by the audience, either remains in a position of feudal nationalism hegemony or holds alternative interpretations of nationalism. The theoretical framework employed in this research is Stuart Hall's Reception Analysis, which positions the audience in three positions: Dominant-hegemonic, Negotiated, and Oppositional. The results obtained from these positions are expected to conclude the characteristics of nationalism held by Indonesian society and the hegemonic power of the media. This research utilizes a qualitative method with a critical paradigm. The data obtained through interviews with the four informants were purposively sampled. The findings of the research indicate that one informant occupies the dominant position, agreeing with the concept presented in the advertisement, two informants are in the negotiated position, offering different interpretations than the advertisement producers, and one informant holds an oppositional position, refuting the concept of the advertisement. The researcher also concludes from this study that the audience tends towards a type of nationalism known as civic nationalism, which is pragmatic in the sense that it focuses on activities held in common as the essence of society's nationalism